(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to analyze the educational values of ethical Sufism (Tasawuf Akhlaki) in the book Al-Hikam by Habib Abdullah Bin Alwi Al-Haddad. The study is motivated by the phenomenon of moral decline among Muslims, especially students. This research employs a qualitative approach with a library research method. Primary data are derived from the original Arabic text of Al-Hikam and its Indonesian translation, while secondary data are obtained from relevant scientific articles, journals, and books. The findings indicate that the ethical Sufism values in Al-Hikam encompass spiritual, moral, and social aspects that play a vital role in shaping individual character. The implementation of these values aligns with the objectives of Indonesia’s National Education System as outlined in Law No. 20 of 2003, emphasizing the development of students into faithful, pious, morally upright, and skillful individuals. These Sufism values also support the creation of an educational environment that balances intellectual and spiritual aspects, contributing positively to the improvement of the young generation’s morality